Giberela em trigo: sobrevivência, reação de cultivares e controle químico - Viana, Eduardo (2013)
A Fusarium Head Blight (FHB) is a disease that attacks various winter cereals, especially wheat and is considered the main spike disease of cereal. The objectives of this study were to observe if the pathogen Gibberella zeae survives in soybean debris, to quantify the incidence of perithecium in the debris, to quantify the incidence of Fusarium graminearum in soybean seeds produced in Rio Grande do Sul, to determine the concentration of conidia of F. graminearum for artificial inoculation into spikelets of wheat and subsequent evaluation of the reaction of wheat cultivars, and to evaluate the best chemical control for FHB in the field using only one fungicides or in mixtures. The experiments were conducted in growth chambers and in the experimental area of the University of Passo Fundo. It was observed that the fungus G. zeae survives in soybean debris. The number of perithecium found in the debris was low probably due to unfavorable climate for their development and maturation, in both years of evaluation. Assessing the health of seeds, it was found that the average incidence of F. graminearum in seeds produced in Rio Grande do Sul in 2011/2012 season was 1.0%. The concentrations of F. graminearum conidia on wheat spikelets, 31x10³ conidia.mL-1 was the concentration in which there was the highest number of infected spikelets in the most susceptible cultivar, being chosen to be used in determining the response of the cultivars. The cultivars responses, the cultivars used were Mirante, Pampeano, BRS 177 and BRS 208. Pampeano and BRS 177 were good sources of FHB resistance type II, unlike Mirante and BRS 208. The chemical control for FHB, there was no differences between fungicide mixture and the control